S-(3-Aminobenzanthron-2-yl)cysteine in the globin of rats as a novel type of adduct and possible biomarker of exposure to 3-nitrobenzanthrone, a potent environmental carcinogen - Linhart, Igor; Hanzlíková, Iveta; Mráz, Jaroslav; Dušková, Šárka (Archives of toxicology, 2017)
3-Nitrobenzanthrone (3-NBA), a potent environmental mutagen and carcinogen, is known to be activated in vivo to 3-benzanthronylnitrenium ion which forms both NH and C2-bound adducts with DNA and also reacts with glutathione giving rise to urinary 3-aminobenzanthron-2-ylmercapturic acid. In this study, acid hydrolysate of globin from rats dosed intraperitoneally with 3-NBA was analysed by HPLC/MS to identify a novel type of cysteine adduct, 3-aminobenzanthron-2-ylcysteine (3-ABA-Cys), confirmed using a synthesised standard. The 3-ABA-Cys levels in globin peaked after single 3-NBA doses of 1 and 2 mg/kg on day 2 to attain 0.25 and 0.49 nmol/g globin, respectively, thereafter declining slowly to 70-80% of their maximum values during 15 days. After dosing rats for three consecutive days with 1 mg 3-NBA/kg a significant cumulation of 3-ABA-Cys in globin was observed. 3-ABA-Cys was also found in the plasma hydrolysate. Herein, after dosing with 1 and 2 mg 3-NBA/kg the adduct levels peaked on day 1 at 0.15 and 0.51 nmol/ml plasma, respectively, thereafter declining rapidly to undetectable levels on day 15. In addition, sulphinamide adducts were also found in the exposed rats, measured indirectly as 3-aminobenzanthrone (3-ABA) split off from globin by mild acid hydrolysis. Levels of both types of adducts in the globin samples parallelled very well with 3-ABA/3-ABA-Cys ratio being around 1:8. In conclusion, 3-ABA-Cys is the first example of arylnitrenium-cysteine adduct in globin representing a new promising class of biomarkers to assess cumulative exposures to aromatic amines, nitroaromatics and heteroaromatic amines.
Keywords: benz(a)anthraceny; Animals; Environmental Biomarkers; cystein; Rats, Wistar; hydrolýza; bioindikátory; vysokoúčinná kapalinová chromatografie; krevní plazma; Carcinogens; magnetická rezonanční spektroskopie; Chromatography, High Pressure Liquid; globiny; Plasma; Male; karcinogeny; Cysteine; Hydrolysis; Globins; Benz(a)Anthracenes; zvířata; mužské pohlaví; Magnetic Resonance Spectroscopy; potkani Wistar